Death seasonality determination from pinnipeds teeth: the Cueva del Negro site case (Argentine Patagonia) - Pablo Ambrústolo; Miguel A. Zubimendi; Enrique Crespo (Arqueologia, 2019)
In this article, we present the first results of the determination of season at death performed over eighteen South American sea lions (Otaria flavescens) teeth recovered at Cueva del Negro site (northern coast of the Santa Cruz Province, Patagonia, Argentina). Age and season of death was determined by growth-layer analysis on sea lion teeth. This analysis allowed us to suggest potential aboriginal hunting strategies regarding the capture of these pinnipeds. Our results indicate that sea lions were hunted between summer and early fall, more precisely between January and April. This would reflect a marked seasonality in relation to sea lion availability, which could be explained in terms of mobility and subsistence strategies of the human groups that inhabited the area. In this sense, our results are discussed taking into consideration paleodietary data and the existing archaeological studies.